2000
DOI: 10.1074/jbc.m001408200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Manganese Lipoxygenase with a Catalytic Mononuclear Redox Center

Abstract: Manganese lipoxygenase was isolated from the takeall fungus, Gaeumannomyces graminis, and the oxygenation mechanism was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
91
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 32 publications
(48 reference statements)
4
91
0
Order By: Relevance
“…At the end of lipoxygenation, 11-HPODE is transformed to 13-HPODE by Mn-LOX (15). Electron paramagnetic resonance analysis suggests that the catalytic metal redox cycles (Mn 21 /Mn 31 ) between the resting and active forms of the enzyme, in analogy with Fe-lipoxygenases, and that the metal coordinating residues are virtually identical (16)(17)(18)(19). To date, the oxygenation of bis-allylic carbons by Fe-lipoxygenases has only been reported for the recombinant lipoxygenase domain of allene oxide synthase of Plexaura homomalla, which transforms 20:3n-6 to the bis-allylic hydroperoxide at C-10 (?5%) and to the allylic hydroperoxide at C-8 (20).…”
mentioning
confidence: 99%
“…At the end of lipoxygenation, 11-HPODE is transformed to 13-HPODE by Mn-LOX (15). Electron paramagnetic resonance analysis suggests that the catalytic metal redox cycles (Mn 21 /Mn 31 ) between the resting and active forms of the enzyme, in analogy with Fe-lipoxygenases, and that the metal coordinating residues are virtually identical (16)(17)(18)(19). To date, the oxygenation of bis-allylic carbons by Fe-lipoxygenases has only been reported for the recombinant lipoxygenase domain of allene oxide synthase of Plexaura homomalla, which transforms 20:3n-6 to the bis-allylic hydroperoxide at C-10 (?5%) and to the allylic hydroperoxide at C-8 (20).…”
mentioning
confidence: 99%
“…0.3-0.7 mol of iron/mol of LOX (47). Mn-LOX on the other hand has been reported to contain 0.94 mol of manganese/mol of enzyme, while iron was below detection limit (40). Interestingly, we observed that upon expression of CspLOX2 under poor iron conditions, manganese can be incorporated in the active site.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have shown that the metal centers of manganese and iron enzymes have otherwise similar properties (40). This rearrangement, however, has been suggested to be related to the higher redox potential of Mn 3ϩ (Mn 2ϩ % Mn 3ϩ ϩe Ϫ , ϳ1.5 V versus Fe 2ϩ % Fe 3ϩ ϩe Ϫ , 0.77 V) (51).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…1A). Gg-MnLOX has been extensively studied since 1998 as the prototype MnLOX (12)(13)(14)(15). The enzyme has been characterized by site-directed mutagenesis of residues, which were chosen from sequence homology to FeLOXs with known 3D structures or from sequence differences between MnLOXs with dissimilar catalytic activities (9)(10)(11)(16)(17)(18)(19).…”
mentioning
confidence: 99%